Design of Autonomous Robots - Hassan, Jana (2025)
The design and build of four robots with the ability to move autonomously to perform challenges and tasks. This was part of the VEX Robotics competition that the students participated in back in February and won the best Design Award over all participating universities in Kuwait and also won third place in the tournament category.